SPECIAL OPERATIONS FORCES OF THE ARMED FORCES OF THE REPUBLIC OF UZBEEKISTAN: IN THE PAST, AT PRESENT, IN THE FUTURE - Lieutenant Colonel Ildar N. Yafarov (American Journals, 2024)
This article analyzes retrospectives and current state of the SOF of the Armed Forces of the Republic of Uzbekistan in comparison with the Special Operations Forces units’ organization and experience of use in the leading foreign armies of the world.